Unsuccessful and Successful Clinical Trials in Acute Respiratory Distress Syndrome: Addressing Physiology-Based Gaps - Villar, Jesús; Ferrando, Carlos; Tusman, Gerardo; Berra, Lorenzo; Rodríguez-Suárez, Pedro; Suárez-Sipmann, Fernando (Frontiers in Physiology, 2021)
Acute respiratory distress syndrome (ARDS) is a life-threatening form of acute hypoxemic respiratory failure characterized by increased vascular permeability pulmonary edema, which causes loss of aerated lung tissue, decreased lung compliance, increased physiological dead space, and hypoxemia. Most patients with ARDS improve their oxygenation, as assessed by the ratio between arterial partial pressure of oxygen and inspired oxygen fraction, with routine intensive care management and after the application of moderate to high levels of positive end-expiratory pressure. However, some patients develop persistent hypoxemia because their lungs are severely injured, remaining unresponsive to high inspiratory fractions of oxygen and increasing levels of positive end-expiratory pressure. For decades, mechanical ventilation, using conventional mechanical ventilators, was the only supportive form of therapy providing adequate oxygenation and carbon dioxide elimination. Mechanical ventilation provides time for disease-specific therapy to reverse the cause of lung injury and for recovery of respiratory function. The adverse effects of conventional mechanical ventilation are the direct consequence of pulmonary pressure and volume changes induced by cyclic mechanical insufflations of diseased lungs or both. In this article, we review 14 major successful and unsuccessful randomized controlled trials conducted in patients with ARDS on a number of alternative techniques to improve oxygenation and ventilation in ARDS patients published since 2010. Those trials tested the effects of adjunctive therapies (neuromuscular blocking agents, prone positioning), methods for selecting the optimum positive end-expiratory pressure (after recruitment maneuvers, or guided by esophageal pressure), high-frequency oscillatory ventilation, extracorporeal oxygenation, and pharmacologic immune modulators of the pulmonary and systemic inflammatory responses in patients with ARDS. We will briefly comment the physiology-based gaps of negative trials and highlight the possible needs to address in future clinical trials in ARDS.